2013
DOI: 10.1111/1574-6941.12116
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of thermal ecotypes and potential pathotypes ofBacillus thuringiensissoil isolates

Abstract: Ecological diversification of Bacillus thuringiensis soil isolates was examined to determine whether bacteria adapted to grow at low temperature and/or potentially pathogenic correspond to genetically distinct lineages. Altogether, nine phylogenetic lineages were found among bacilli originating from North-Eastern Poland (n = 24) and Lithuania (n = 25) using multi-locus sequence typing. This clustering was chiefly confirmed by pulsed-field gel electrophoresis. One third of the bacilli were found to be psychroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
3
24
1
1
Order By: Relevance
“…In this study we found lineages of isolates, mostly within clade III, capable of growth at low temperature (thermal ecotypes), as previously observed among B. cereus s.l. and B. thuringiensis [30], [56]. However, in contrast to the previous report [30], in which we found association between the cytotoxic potential with some B. thuringiensis ecotypes, in this study the presence of cytK was mainly associated with isolates from farm samplings where human activity is extensive, while the gene was absent in isolates originating from Białowieża NP.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study we found lineages of isolates, mostly within clade III, capable of growth at low temperature (thermal ecotypes), as previously observed among B. cereus s.l. and B. thuringiensis [30], [56]. However, in contrast to the previous report [30], in which we found association between the cytotoxic potential with some B. thuringiensis ecotypes, in this study the presence of cytK was mainly associated with isolates from farm samplings where human activity is extensive, while the gene was absent in isolates originating from Białowieża NP.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the above hypothesis was not confirmed in our study as (i) only seven STs included bacilli classified into different species, (ii) the isolates classified to the same species but originated from different habitats exhibited a tendency of clustering to particular complexes, and (iii) B. mycoides isolates showed higher genetic similarity than B. cereus s.s. and B. thuringiensis confirmed statistically by significantly lower number of clonal complexes with high number of isolates (4 CCs; N = 78/84). The previous reports largely focused on B. cereus s.s. , B. anthracis , and/or B. thuringiensis [12], [28], [30]. Here we present for the first time the genetic structure for B. mycoides .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…species makes their classification troublesome17. Therefore, several studies suggested that the B. cereus group should be considered as a single evolutionary unit characterized by clonal expansion and adaptation to various hosts and/or environments that possibly led to the formation of distinct phenotypes, also called ecotypes, within major phylogenetic lineages141819.…”
mentioning
confidence: 99%